Assessment of a porcine circovirus type 2 vaccine prototype through anatomopathological analysis and its correlation with blood viral load - Larenas-Muñoz, Fernanda; De Barbieri, Paloma; Mellado, César; Reyes, Fátima; Toledo, Jorge; Neira, Víctor; Lamazares, Emilio; Ruiz-Garrido, Alvaro (Frontiers in Veterinary Science, 2026)
Porcine circovirus type 2 (PCV2) is an endemic pathogen of global relevance, responsible for porcine circovirus-associated diseases (PCVAD). Consequently, vaccination against PCV2 is a standard practice in intensive swine production systems. This study aimed to evaluate the effect of a prototype vaccine on PCV2 viral load and associated lesions. Thirty-nine pigs from a high-health-status farm were randomly assigned to three experimental groups (n = 13 per group), corresponding to a placebo group, a commercial vaccine group and a prototype vaccine group. Viral load was assessed by qPCR from serum samples, while lesions were evaluated through necropsy and histopathological analysis of lymph nodes and lungs tissue. No statistically significant differences in viral loads were observed among the three groups, and most animals did not exhibit detectable viremia. However, the placebo group showed more numerous and severe lesions in lymph nodes and lungs compared to the vaccinated groups, with the commercial vaccine group showing milder lesions than the prototype vaccine group. These findings suggest that the absence of viremia in most animals may reflect the timing of infection or effective containment by host immunity. Both the commercial and prototype vaccines were associated with reduced lesion severity, although the prototype vaccine demonstrated an intermediate performance between the placebo and commercial vaccine groups. Further development and optimization of the prototype formulation are warranted to enhance its protective efficacy.